Issues and Perspectives on Cyberterrorism and Information Security in Nigeria - Kente, Josiah Sabo; Ishaku, Jesse (ALSYSTECH Journal of Education Technology, 2024)
The advent of information and communication technology (ICT) and the internet in Nigeria offer endless opportunities and also raise a lot of concerns bothering on cybercrime, cyberterrorism, information and human security. Recently, Nigeria has experienced an unprecedented surge in cybercrime, with potentially disastrous consequences for the country's socioeconomic and sustainable growth. Consequently, the complexities and horrific nature of cyberterrorism in recent times have increased proportionately which calls for prompt action. This study therefore, examines the effects of cyberterrorism on information and human security in Nigeria. Anchored on the technology-enabled crime and risk society theory and integrative literature review approach, the study revealed that, aside from the fact that information security is important for the continued existence of individuals, organisations and government in Nigeria, different terrorist and secessionist groups in Nigeria such as Boko Haram have been using the Nigeria’s cyberspace to mobilize and train its members, raise funds as well as propagate their nefarious agenda. The study however recommends among many things that, the Nigerian government should strengthen the Cybercrime Prohibition and Prevention Act 2015 while also ensuring the establishment of strong legal, institutional and security frameworks in line with the United Nations Security Council Resolution 2341 (2017) and the United Nations Global Counter-Terrorism Strategy (GCTS) in order to fight cyberterrorism in Nigeria.